Global and mid-latitude impact of ten years of solar activity using observational data of the geophysical and astronomical observatory of the University of Coimbra - Castillo Rosales, Yvelice Soraya (2018)
Tese de doutoramento em Física, na especialidade de Astrofísica, apresentada ao Departamento de Física da Faculdade de Ciências e Tecnologia da Universidade de Coimbra